2014
DOI: 10.1039/c3ay41094c
|View full text |Cite
|
Sign up to set email alerts
|

Looking beneath Dalí's paint: non-destructive canvas analysis

Abstract: A new analytical method was developed to non-destructively determine pH and degree of polymerisation (DP) of cellulose in fibres in 19 th -20 th century painting canvases, and to identify the fibre type: cotton, linen, hemp, ramie or jute. The method is based on NIR spectroscopy and multivariate data analysis, while for calibration and validation a reference collection of 199 historical canvas samples was used. The reference collection was analysed destructively using microscopy and chemical analytical methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…It is therefore safe to assume that environmental pollution is not going to represent a major source of acidification in the near future. Local staining and discolouration does not seem to result in significantly higher local acidity either (Oriola et al, 2014), which would mean that future acidification is likely going to be a consequence of natural degradation processes inherent to canvas. It is of interest to compare MNAC averages with the data obtained from the survey of 12 Dalí paintings from Teatre-Museu Dalí, Figueres, Spain (Oriola et al, 2014).…”
Section: Museu Nacional D'art De Catalunya Surveymentioning
confidence: 99%
See 4 more Smart Citations
“…It is therefore safe to assume that environmental pollution is not going to represent a major source of acidification in the near future. Local staining and discolouration does not seem to result in significantly higher local acidity either (Oriola et al, 2014), which would mean that future acidification is likely going to be a consequence of natural degradation processes inherent to canvas. It is of interest to compare MNAC averages with the data obtained from the survey of 12 Dalí paintings from Teatre-Museu Dalí, Figueres, Spain (Oriola et al, 2014).…”
Section: Museu Nacional D'art De Catalunya Surveymentioning
confidence: 99%
“…Several measurements were made per canvas, typically up to 7, and the average is reported. Using the canvas identification algorithm based on linear discriminant analysis of NIR spectra (Oriola et al, 2014), bast, cotton, and jute fibres were identified, however, out of the 31 surveyed paintings, only 3 were made of jute and 3 were made of cotton fibres, the rest were all made of bast fibres.…”
Section: Nir Measurementsmentioning
confidence: 99%
See 3 more Smart Citations